A novel compact dual-band bandstop filter with enhanced rejection bands - Ayyoub El Berbri; Hassna Agoumi; Seddik Bri; Youssef El Amraoui; Adil Saadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
In this paper, we present the design of a new wide dual-band bandstop filter (DBBSF) using nonuniform transmission lines. The method used to design this filter is to replace conventional uniform transmission lines with nonuniform lines governed by a truncated Fourier series. Based on how impedances are profiled in the proposed DBBSF structure, the fractional bandwidths of the two 10 dB-down rejection bands are widened to 39.72% and 52.63%, respectively, and the physical size has been reduced compared to that of the filter with the uniform transmission lines. The results of the electromagnetic (EM) simulation support the obtained analytical response and show an improved frequency behavior.